CNS Complications of Systemic Malignancy amongst patients attending a Radiotherapy facility in Lagos - Popoola, A.O.; Igwilo, A.I.; Idowu, O.; Ketiku, K.K.; Duncan, K.J.T. (Asian Journal of Medical Sciences, 2014)
Introduction: The Central nervous system (CNS) is a frequent a site of relapse of systemic cancer. There are few data available in literature about the frequency and nature of symptomatic histopathological variants of secondary brain/spinal tumours drawn against the gender/age distribution in our environment. Objective: To study the frequency and manifestation of CNS involvement in patients with systemic cancer for a high index of suspicion so that practitioner will have highest index of suspicion to make early diagnosis and treatment in our environment. Material and methods: A total of 119 patients with histological confirmed cases of cancer with secondaries to the CNS, were analysed for this study. Results: CNS metastasis were more common in female (67%) than male (33%) p=0.047. Spinal cord metastasis is the most common type of neurological manifestation (66.9%) with p=0.011. Breast (60.5%) and prostate (21%) were the most common site of primary tumour. Neurological manifestations were mostly associated with advanced Stage tumours (54.9%) (p=0.000). Approximately half of the cases, 56 (54.9%) were presented at late stage (4). Neurological manifestation occurred <6 months (43.1%) after initial diagnosis of the primary tumour. Spinal/radicular pain was the most prevalent among the patients (43%). CT scan/MRI Imaging in (52.6%) and mode of treatment was radiotherapy (99%) of patients. Conclusion: Even though therapy is largely palliative, research should focus on enhancing the efficacy of whole brain radiotherapy and invest in the biosynthesis of synergistic new systemic agents that could also cross the BBB. DOI: http://dx.doi.org/10.3126/ajms.v6i4.11805 Asian Journal of Medical Sciences Vol.6(4) 2015 55-60